Effectiveness of Acupuncture in the Treatment of Parkinson's Disease: An Overview of Systematic Reviews - Huang, Jinke; Qin, Xiaohui; Cai, Xiaowen; Huang, Yong (Frontiers in Neurology, 2020)
Background: The effects of acupuncture on Parkinson’s disease (PD) outcomes remain unclear. The aim of this overview was to comprehensively evaluate the methodological quality and applicability of the results of systematic reviews (SRs)/meta-analyses (MAs) that examined the use of acupuncture to treat PD. Methods: Eight databases were searched to retrieve SRs/MAs on the use of acupuncture to treatment for PD. Two reviewers independently screened and extracted the data using the Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2) checklist to evaluate the methodological quality and, using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) criteria to assess the evidence quality of the included reviews. Results: A total of 11 SRs/MAs were included. According to the AMSTAR-2 checklist results, all included SRs/MAs were rated as very low-quality studies. The GRADE criteria revealed 20 studies with very low-quality evidence, 9 with low-quality evidence, 3 with moderate-quality evidence, and 0 with high-quality evidence. Descriptive analysis showed that acupuncture appears to be a clinically effective and safe treatment for PD. Conclusions: The use of acupuncture for the treatment of PD may be clinically effective and safe. This conclusion must be interpreted cautiously due to the generally low methodological quality and low quality of evidence of the included studies.